Smooth sliding control and extremum seeking applied to wind turbines - Pacheco, Gabriel Felippe da Cruz (2018)
This study addresses the application of extremum seeking control (ESC) in an outer loop to perform the maximum power point tracking (MPPT) in wind energy conversion systems (WECS). For the case when power measurements are not available, a torque or power estimation scheme is proposed. This optimization algorithm is categorized as a Hill Climb Search (HCS) control and does not require any measurement or estimation of the wind speed nor previous knowledge about the turbine’s power-curve. It is also designed a nonlinear robust controller for the inner loop in order to achieve global practical tracking of the turbine’s rotor speed. The robust part of the controller, which maintains fast transient response, is based on sliding mode control that features a smooth control signal (SSC), free of chattering, previously designed for linear plants with arbitrary relative degree. In this sense, this work presents a first generalization of this controller for the class of nonlinear plants representing the WECS dynamics. Moreover, the proposed robust inner loop control does not require measurements of the stator flux nor any flux observer. The controller is designed by using an inherent stability property of the WECS dynamics demonstrated in this document, named, the input-to-state stable with respect to the turbine angular velocity and its time derivatives. The closed-loop stability analysis is provided considering the WECS with an inner loop with SSC and an outer loop with a variation of the ESC based on sinusoidal perturbations. The effectiveness of the proposed scheme is supported by analysis and simulation results.